Advances in the bonded composite repair of metallic aircraft structure. - Baker, A. A. (Alan A.); Rose, L. R. F.; Jones, R. (Rhys)
The availability of efficient and cost-effective technologies to repair or extend the life of aging military airframes is becoming a critical requirement in most countries around the world, as new aircraft becoming prohibitively expensive and defence budgets shrink. To a lesser extent a similar situation is arising with civil aircraft, with falling revenues and the high cost of replacement aircraft. This book looks at repair/reinforcement technology, which is based on the use of adhesively bonded fibre composite patches or doublers and can provide cost-effective life extension in many situatio.